Cultural evidence for interpretation bias as a feature of social anxiety in Chinese adolescents. Issue 4 (4th July 2019) - Yu, Meng; Westenberg, P. Michiel; Li, Wei; Wang, Jianping; Miers, Anne C.
ABSTRACT: Background and Objectives: Interpretation bias (IB), defined as the tendency to interpret ambiguous social situations in a threatening manner, has increasingly been studied in children and adolescents. Compared to Western samples, the relation between IB and social anxiety in Chinese youth has received little attention. The present study was to mainly examine the relationship between IB and social anxiety among Chinese adolescents. Design: Cross-sectional design was utilized. Methods: IB, measured by the Adolescents' Interpretation Bias Questionnaire (AIBQ), and social anxiety were surveyed among a group of high socially anxious Chinese adolescents ( n = 25) and a control group ( n = 29). Participants were asked to rate the likelihood of interpretations coming to mind in social/non-social situations and to choose the most believable interpretation. Results: The high social anxiety group had more negative interpretations and beliefs in social situations, and the interpretation bias was particular to social anxiety versus depression. Additionally, the cognitive content-specificity hypothesis was supported; the high anxious group showed interpretation bias in social situations, but didn't have more negative interpretations of non-social situations, after controlling for depression. Conclusions: The present study yielded comparable findings as found in Western samples regarding the relation between IB and social anxiety.